Guillain-Barré syndrome following falciparum malaria infection: a case report - Molla Asnake Kebede; Alemayehu Beharu Tekle; Misikir Alemu Eshetu; Erkyehun Pawlos Shash; Melaku Tsediew Berhanu; Elias Tabiet Ahmed; Hashime Meketa Negatie (BMC Neurology)
Abstract Background Malaria is an infectious disease caused by Plasmodium parasites, transmitted to humans by infected female Anopheles mosquitoes. Five Plasmodium species infect humans: P. vivax, P. falciparum, P. ovale, P. malariae, and P. knowlesi. Guillain-Barré Syndrome (GBS) is an inflammatory condition that can lead to paralysis, autonomic dysfunction, respiratory failure, and sensory symptoms. GBS typically follows an infection with Campylobacter bacteria, commonly found in undercooked poultry, but is rarely associated with malaria. Clinical presentation A 16-year-old female patient presented to our emergency department with a 1-day history of altered mentation. She had experienced a severe global headache and fever for 3 days prior to presentation. The patient tested positive for falciparum malaria and was admitted to the ward, where she received IV artesunate and other supportive management. After 3 days of admission, she noticed weakness and numbness in her lower extremities. Subsequently, the weakness progressed upward to involve her upper extremities. After extensive workup, the patient was managed with consideration of Guillain-Barré Syndrome (GBS), and she made a complete recovery after 12 weeks. Discussion Guillain-Barré Syndrome (GBS) is an acute paralytic illness often triggered by infections, particularly viral ones. It is the leading cause of sudden muscle weakness, typically following respiratory or gastrointestinal infections, with Campylobacter jejuni being the most common cause. This patient’s neurological symptoms pointed to paralysis of the lower motor neurons. Guillain-Barré Syndrome is also suggested by elevated protein levels and a lack of cells in the cerebrospinal fluid. This clinical picture emerged following a Plasmodium falciparum infection. Although the specific subtype (demyelinating or axonal) was not determined in this case due to the absence of a nerve conduction study, demyelinating subtypes have been found in GBS following Plasmodium infection. Conclusion In conclusion, while malaria is an exceptionally rare cause of Guillain-Barré Syndrome (GBS), it should be considered in patients with recent malaria infection who present with symptoms of lower motor neuron lesions.